Pegustian dan Temenggung : akar sosial, politik, etnis, dan dinasti perlawanan di Kalimantan Selatan dan Kalimantan Tengah, 1859-1906 - Sjamsuddin, Helius, 1938- (Jakarta : Balai Pustaka, 2001)
History of independence war of Banjarmasin Sultanate against Dutch colonialism in South and Central Kalimantan, 1859-1906
Translation of the author's thesis (doctoral-Monash University, Australia, 1989) originally presented under the title: Fighting Dutch rule in the nineteenth and early twenteenth centuries: the social, political, ethnic, and dynastic roots of resistance in South and Central Kalimantan, 1859-1906
Includes bibliographical references (p. 520-569)
Keywords: Bandjermasin (Sultanate) -- History; Kalimantan Selatan (Indonesia) -- History; Kalimantan Tengah (Indonesia) -- History